2021
DOI: 10.3389/fphar.2021.679407
|View full text |Cite
|
Sign up to set email alerts
|

Dynamic Modeling of Mitochondrial Membrane Potential Upon Exposure to Mitochondrial Inhibitors

Abstract: Mitochondria are the main bioenergetic organelles of cells. Exposure to chemicals targeting mitochondria therefore generally results in the development of toxicity. The cellular response to perturbations in cellular energy production is a balance between adaptation, by reorganisation and organelle biogenesis, and sacrifice, in the form of cell death. In homeostatic conditions, aerobic mitochondrial energy production requires the maintenance of a mitochondrial membrane potential (MMP). Chemicals can perturb thi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
14
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 18 publications
(16 citation statements)
references
References 50 publications
2
14
0
Order By: Relevance
“…The next-generation chemical risk assessment paradigm stimulates the use of mechanism-driven studies in which biology-relevant parameters are quantified using sophisticated unbiased assessment methods and integrated into networks of prediction models (Krewski et al 2014). The data obtained in this study fits this type of risk assessment, when combined with for instance ordinary differential equations (ODEs) to describe the time and concentration dependency of the ATP and MMP alterations (Yang et al 2021, Daun et al 2008. Such modeling efforts will result in threshold values describing the concentration, moment in time, or the effect size at which one event will trigger the next.…”
Section: Discussionmentioning
confidence: 87%
“…The next-generation chemical risk assessment paradigm stimulates the use of mechanism-driven studies in which biology-relevant parameters are quantified using sophisticated unbiased assessment methods and integrated into networks of prediction models (Krewski et al 2014). The data obtained in this study fits this type of risk assessment, when combined with for instance ordinary differential equations (ODEs) to describe the time and concentration dependency of the ATP and MMP alterations (Yang et al 2021, Daun et al 2008. Such modeling efforts will result in threshold values describing the concentration, moment in time, or the effect size at which one event will trigger the next.…”
Section: Discussionmentioning
confidence: 87%
“…This result indicates that oxidative stress contributes to pancreatic cancer apoptosis, suggesting that ivermectin may represent a therapeutic alternative for pancreatic cancer. As ROS reduce MMP and OCR by damaging mitochondria (Yang et al, 2021), the MMP and OCR values in the combination treatment group and gemcitabine alone group Mitochondrial biosynthesis is important for maintaining mitochondrial homeostasis, which is crucial for cell survival (Ma et al, 2020). Cancer induces mitochondrial fission and mitophagy to eliminate dysfunctional mitochondria, which can lead to cell death (Martinez-Outschoorn et al, 2011;Chourasia et al, 2015).…”
Section: Discussionmentioning
confidence: 99%
“…In the FA-enriched conditions, UCP1 expression was repressed likely to avoid an excessive amount of inducible proton leak under high MMP. This feedback regulation was supported by the perturbation of MMP using oligomycin and FCCP [36,37]. These results suggested that a unique regulatory mechanism underlying UCP1 expression and mitochondrial-energy status was altered by FA availability in human brown adipocytes.…”
Section: Discussionmentioning
confidence: 74%